A New Robotic Application for COVID-19 Specimen Collection Process - Cengiz Deniz; Gürsel Gökmen (Journal of Robotics and Control (JRC), 2022)
Covid-19 manual specimen collection process is too critical for health care workers due to they are able to getting infection from Covid-19-patient during the medical interaction. The purpose of this study, a novel robotic application is developed to achieve automatic specimen collection process for new corona virus (COVID-19). This application is a protection tool for health care workers for the Covid-19 pandemic. This robotic application easily and safely complete the sampling process task and assist to health care workers to prevent infection. The application is basically consist of a collaborative robot (COBOT), base plate, fixtures and a gripper. There are co-operation activities between the COBOT and health care worker to complete all tasks. The robotic application has been tested in the plant health care center as a prototype. The cycle-time (192 sec) for the robotic process needs to be improved. The Manual process is still %60 faster than robotic application. The biggest challenge in this application is patient’s mouth and nose physical size changes. Robot movements for the specimen collection in nose and mouth are arranged just based on the fixed point. This needs to be improved according to size changes. Covid-19 specimen collection process with a robotic application has been presented which don’t need any health care worker interaction with patient. This application needs to be improved related with above challenges to make a shelf product. It will create valuable impact and save lives in this pandemic.